1976
DOI: 10.1002/1097-0142(197604)37:4<1643::aid-cncr2820370404>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic enhancement of nitrogen mustard cytotoxicity in mouse leukemia

Abstract: Mouse leukemia L1210 cells were exposed to continuous wave 2 MHz, 10 W/cm(2) ultrasound for 10 minutes while suspended in nitrogen mustard solution in vitro. Mice subsequently inoculated with these cells had longer survival times than control animals that received cells exposed to the drug but not ultrasound. Without the drug, ultrasound did not alter survival time. Tracer studies revealed increased cellular accumulation of drug under the influence of ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 5 publications
1
29
0
Order By: Relevance
“…Several reports have reveled ultrasound is able to enhance the anticancer effect of some chemotherapeutic drugs. Kremkau et al also found that ultrasound irradiation could potentiate the cytotoxic effect of various drugs, such as nitrogen mustard, in murine leukemia L1210 cells [4]. Similar results have been obtained from the experiments performed by Harrison and Balcer-Kubiczek [5].…”
Section: Introductionsupporting
confidence: 61%
“…Several reports have reveled ultrasound is able to enhance the anticancer effect of some chemotherapeutic drugs. Kremkau et al also found that ultrasound irradiation could potentiate the cytotoxic effect of various drugs, such as nitrogen mustard, in murine leukemia L1210 cells [4]. Similar results have been obtained from the experiments performed by Harrison and Balcer-Kubiczek [5].…”
Section: Introductionsupporting
confidence: 61%
“…Mice subsequently inoculated with these cells had longer survival times than control animals that received cells exposed to the drug but not ultrasound. [27]…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The cytotoxic effect of nitrogen mustard on mouse leukemia L1210 cells after sonication without any mechanical damage to cells was observed (Kremkau et al 1976). Tumors implanted into the hamster flank and sonicated with the co-administration of a chemotherapeutic (BCNU) improved the survival rate from 29.4% (sonication alone) to 40% (Fry and Johnson 1978).…”
Section: Introductionmentioning
confidence: 99%